"Your meal is ready" notifier @ Customer Call System / Adiba Abd Ghafar and Siti Khadijah Shamsuddin - Abd Ghafar, Adiba; Shamsuddin, Siti Khadijah (2015)
Nowadays, table call system has been known widely in most restaurant industries. However, a difference can be made by developing a customer relationship management for counter and self-collection operation. Today, restaurants are crowded with people entering and leaving the restaurant. However, the restaurant system is not well-organized during peak meal times. The queue of taking orders at the counter will be long. Moreover, waiters will be outnumbered thus causing people to wait for a long period of time. A system needs to be developed that would help Inform customers when their meal is ready allowing customers to tolerate longer wait times. This project is applicable at food courts, restaurants, cafes and self-service counters as it offers a solution to eliminate long lines and chaotic crowds during peak meal times. Customers are free to wait at the table, knowing that they will be notified automatically when their foods are ready to collect from the counter. This project is using the concept of transmit and receive. It will only function if both system works as they are linked using PIC16F877A.The transmitter will transmit the data to the receiver (a device given to the customer) by pushing the push buttons. When the receiver receives the data, the customer will be notified that their foods are ready. There will be two message displays which are "Please wait :)" and "Meal is ready!". LED will blink and the buzzer will tum on